Material Procurement in Construction Industry Problems and Solutions - Subramani, T; Prabhu, A (International Journal of Engineering and Technology, 2018)
Good project management in construction means efficient utilization of labor, material and equipment. Development of labor productivity have to be a first-rate and chronic challenge of those who are accountable for cost control of constructed facilities. Material handling, which includes procurement, inventory, shop fabrication and field servicing, requires special attention for cost reduction. The use of latest equipment and progressive strategies has made feasible wholesale adjustments in construction technology in current a long time. Groups which do no longer recognize the effect of diverse innovations and feature now not adapted to changing environments have justifiably been compelled out of the mainstream of construction activities. The frequent problems of construction industry, customers have an essential position to play. With the aid of its procurement methods, the purchaser impacts the manner a construction project is done, because the tactics affect the form of the project delivery system. What sort of procurement procedures are perceived rational, for one, depends at the underlying assumptions about the characteristic of procurement. A recognized guideline in Lean construction (LC) is that production must be conceived along with transformations (T), flow (F), and value generation (V). Alternatively, it is visible necessary to recognize and cope with the risk of value loss with an identical diligence as the other issues had been to date. Materials management plays an important role in project planning and control. Materials represent a major expense in construction, so minimizing procurement or purchase costs.